The patient perspective on remote monitoring of cardiac devices: a german patient survey. (19th May 2022) - Hillmann, HAK; Hansen, C; Przibille, O; Duncker, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Current guidelines recommend remote monitoring for patients with implanted cardiac devices. Nevertheless, data regarding patients' attitude using remote monitoring is lacking. This study aims to analyze the patient perspective on remote monitoring of cardiac devices in Germany. Methods: Patients with an implanted cardiac device and remote monitoring (continuous device follow-up and remote device follow-up) of all current manufacturers in three German centers were asked to participate in the study filling in a patient questionnaire between 07-11/2021. The questionnaire consisted of 37 questions regarding patient's baseline characteristics, individual use and judgement on remote monitoring, as well as the patient's opinion regarding future remote monitoring perspectives. Survey participation was anonymous and on a voluntary basis. Results: 617 patients (28.4 % women) out of three cardiac centers in Germany participated. Implanted cardiac devices were pacemakers ± cardiac resynchronization therapy (CRT) (11.9%), implantable defibrillators ± CRT (70.3%) and implantable loop recorders (17.8%). Technical problems with remote monitoring transmitter were reported to occur: never (60.3%), seldomly (25.5%), sometimes (12.0%) and all the time (2.2%). The majority of patients (84.9%) take part in remote monitoring without the help of others. After starting remote monitoring, patients reported a significant prolongation of the intervals (p<0.001) of their in-person follow-up visits (figure 1). 44.0% of the participating patients answered to have a better, 1.2% a worse and 54.8% an equal disease management since participating in remote monitoring. Regarding possible future perspectives using remote monitoring, 73.0% patients answered to own a smartphone. 48.3% of the patients would prefer a smartphone-based application for remote monitoring. 15.0% had no opinion on that question, whereas 36.7% would prefer the use of a transmitter in their bedroom. Conclusion: In this patient survey, remote monitoring was a widely accepted tool for patients with implanted cardiac devices. Patients perceive an improvement of their disease management through telemonitoring. Furthermore, patients answered that intervals of outpatient visits could be prolonged by the use of remote monitoring. Most patients would appreciate a smartphone-based remote monitoring of their cardiac device.